2015
DOI: 10.18276/cej.2015.3-05
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Match Performance of Full-backs from Selected European Soccer Leagues

Abstract: Abstract. The aim of the present study was the analysis of match activities of full-backs from selected European national soccer leagues. The study sample comprised 30 full-backs playing in the autumn round of the 2014/15 season from five European national top-tier leagues: English Premier League, Spanish Primera Division, German Bundesliga, Russian Priemjer Liga and Italian Serie A. The performance of full-backs (left-back and right-back) from each selected team was analyzed using a professional match analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The same study also found that FB was another position with greater ACC DIS covered (714 ± 298 m) than MF (559 ± 232 m) [20]. This suggests that playing in the lateral side of the pitch in addition to the offensive and defensive roles of FB let this position cover longer ACC DIS compared to central playing positions such as MF [28].…”
Section: Discussionmentioning
confidence: 73%
“…The same study also found that FB was another position with greater ACC DIS covered (714 ± 298 m) than MF (559 ± 232 m) [20]. This suggests that playing in the lateral side of the pitch in addition to the offensive and defensive roles of FB let this position cover longer ACC DIS compared to central playing positions such as MF [28].…”
Section: Discussionmentioning
confidence: 73%
“…Full-backs from the Spanish La Liga performed the most passes, crosses and ball touches in the attacking zone (Konefał et al, 2015). They also executed the lowest number of passes in the midfield and defense zones.…”
Section: Discussionmentioning
confidence: 98%
“…to their counterparts in the English Premier League, Spanish La Liga, and Italian Serie A (Konefał et al, 2015). This would encourage their opponents to adopt counterattacking tactics since the players lost ball possession in the defensive and midfield zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in preferred dribbling direction may result in the asymmetry of centripetal force generated for the performance of the action [25]. In addition, it should be noted that match running performance could possibly be dependent on factors such as trained schemes of offensive actions (e.g., taking part in every offensive action or only during these actions, which are played on a chosen side of the pitch) or tactical tasks during the defensive phase of the game [31,43].…”
Section: Discussionmentioning
confidence: 99%